Preparation, Structure, Function, and Application of Dietary Polysaccharides from Polygonatum sibiricum in the Food Industry: A Review - Peilin Li; Huimin Yao; Hao Yue; Jiali Huang; Qi Wang; Chuanbo Ding; Lina Ma; Xinglong Liu; Min Yang (Molecules)
Polygonatum sibiricum is one of the most widely used plants in the Liliaceae family, renowned for its dual medicinal and edible properties. Polygonatum sibiricum polysaccharides, as the main pharmacological active ingredient of Polygonatum sibiricum, have various excellent physiological activities, such as antioxidant, immune enhancement, and hypoglycemic activities. Through extraction, purification, and structural analysis, the influence and mechanism of the molecular weight and glycosidic bonds of Polygonatum sibiricum polysaccharides on the pharmacological effects, as well as their structure–activity relationship, can be explored in more detail. With the increasing demand for Polygonatum sibiricum polysaccharide products, Polygonatum sibiricum has been widely used in the fields of medicine, food, and biochemistry, and various green and harmless products containing Polygonatum sibiricum polysaccharides have been developed for different populations. This study summarizes the extraction, structure, and function of Polygonatum sibiricum polysaccharides, and it further explores their applications in the food industry, including in beverages, health foods, additives, and food packaging. Overall, Polygonatum sibiricum polysaccharides have been proven to be a promising natural product and have been introduced into the food system. It is worth mentioning that further efforts and time are needed in the future to expand the deep processing of and feasibility research on Polygonatum sibiricum polysaccharides while exploring their bioactive molecular mechanisms in depth, laying the foundation for their product development and clinical applications.